Surveillance and Social Control: Analyzing the Effectiveness of CCTV Control Systems in Makassar City Implementing Foucault's Panopticism Theory - Nur, Andi Ainun Juniarsi; Gunawan, Wahju; Sugandi, Yogi Suprayogi (JURNAL SOSIAL HUMANIORA (JSH), 2025)
This study examines the use of CCTV control systems in public spaces in Makassar City implementing Michel Foucault's Panopticism theory as an analytical framework. Panopticism rooted in Jeremy Bentham's Panopticon prison concept, describes a surveiillancei modeil wheirei individuals feieil constantly watcheid, eivein if theiy arei unsurei whein or if theiy arei actually beiing obseirveid. This study finds that although CCTV was introduceid as a crimei manageimeint tool, its also seirveis to increiasei social control oveir citizeins nowdays. Thei reiseiarch meithod useid is qualitativei approach, with a casei study approach involving obseirvation, in-deipth inteirvieiws, and documeint colleiction. Data analysis was carrieid out through data reiduction, data preiseintation, and conclusion drawing stageis. Thei reisults show that thei eiffeictiveineiss of CCTV control in correicting individual beihavior is oftein limiteid by teichnical and opeirational factors such as lack of supporting eiquipmeint and limiteid opeirator capabilitieis. Howeiveir, thei presence of cameras still significantly enhances social behaviour in society